Training on Coffee Preparation and Production Cost Calculation - Alhamdi, Rezki; Saputra, Eryd; Aurora Mikasari, Dewi; Hasib Bimantara, Muhammad (JURNAL KEKER WISATA, 2025)
As a manifestation of the implementation of the Tri Dharma of Higher Education, Batam Tourism Polytechnic carried out a Community Service (PKM) activity at SMK Swasta Al-Jabar, located in Bengkong Laut Sub-district, Bengkong District, Batam City. This activity involved training in coffee beverage preparation and production cost calculation, with the participation of lecturers and students who are competent in food and beverage management, particularly in the financial aspects of business operations. The primary goal of this training was to enhance students' knowledge and practical skills in beverage production and effective cost management. The training materials covered the selection of quality raw materials, calculation of production costs, pricing strategies, and profit analysis. Participants were also introduced to the concept of unit cost for contemporary beverages such as coffee. The training was conducted interactively through discussions, simulations, and the use of cost calculator tools. The results showed that students were able to understand and apply the fundamental concepts of beverage production and financial management independently. This program is expected to improve students' work readiness and foster their entrepreneurial spirit. Moreover, the activity reflects Batam Tourism Polytechnic’s ongoing commitment to strengthening collaboration with educational institutions to develop competent, independent, and industry-ready young generations